Lattice Imperfections in Intermetallic Ti-Al alloys: an X-Ray Diffraction study of the microstructure by the Rietveld method - Lee Liu Mei (Universiti Malaysia Perlis, 2008)
Microstructure in intermetallic Ti-Al alloys with compositions of Al= 45, 50, 55, and 60% in the homogenized bulk states has been extensively studied using Rietveld whole X-ray profile fitting technique, adopting the recently developed softwares, C-Rietan2000 and MAUD (Material Analysis Using Diffraction). The respective microstructures were observed under SEM (Scanning Electron Microscopy) and EDS (Energy Dispersive Spectroscopy). The Vickers microhardness and density values of the samples were determined. The analysis also considers the quantitative estimation of different phases and lattice defect related features of the evoluted microstructures, namely crystallite sizes and microstrains in the bulk homogenized state. The values of all the above defect parameters have been evaluated and compared for elucidating a better structure-property relationship.